2018
DOI: 10.1002/jlb.2mr1217-503r
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling our concept of chemokine receptor function: From monomers to oligomers

Abstract: The chemokines direct leukocyte recruitment in both homeostatic and inflammatory conditions, and are therefore critical for immune reactions. By binding to members of the class A G protein-coupled receptors, the chemokines play an essential role in numerous physiological and pathological processes. In the last quarter century, the field has accumulated much information regarding the implications of these molecules in different immune processes, as well as mechanistic insight into the signaling events activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 119 publications
(224 reference statements)
1
17
0
Order By: Relevance
“…This is best exemplified by an earlier study using cells co-expressing CXCR4 and CCR5 in combination with selective receptor antagonists (AMD3100 and maraviroc, respectively) ( 52 ). Finally, similar to chemokines in solution, chemokine receptors themselves are known to form dynamic aggregates through lateral movements on cell surfaces, which are thought to modulate ligand selectivity and transmembrane signaling properties ( 53 ). Chemokine receptor-mediated synergism has been difficult to prove, not least because of the diversity of GPCRs present on immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is best exemplified by an earlier study using cells co-expressing CXCR4 and CCR5 in combination with selective receptor antagonists (AMD3100 and maraviroc, respectively) ( 52 ). Finally, similar to chemokines in solution, chemokine receptors themselves are known to form dynamic aggregates through lateral movements on cell surfaces, which are thought to modulate ligand selectivity and transmembrane signaling properties ( 53 ). Chemokine receptor-mediated synergism has been difficult to prove, not least because of the diversity of GPCRs present on immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence showed that Cxcl13 and Ccl2 are known to be involved in pathogenesis of neuropathic pain via different forms of neuron-glia interaction in the spinal cord [ 20 , 21 ]. The chemokines by binding to the G protein-coupled receptors play an essential role in pathological pain conditions triggered by either peripheral inflammation or nerve injury [ 23 , 24 ]. Our results demonstrated that chemokine genes showed the greatest upregulation, such as Cxcl13 (6.426 fold increase), suggesting that chemokines play a crucial role in the development of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Robertson et al, (9) highlighted specifically the challenges of 'deconvoluting physiologically relevant dimerization interfaces from those that simply mediate crystal contacts' and this question has recently been the subject of review (10). Chemokine receptors represent a family of GPCRs for which there is strong evidence of 'dimerization' (11). CXCR4 has been particularly well studied, because of its roles in cancer and viral infections, including its function as a co-receptor for strains of the HIV-1 virus (12,13,14).…”
Section: Introductionmentioning
confidence: 99%